Post-quantum distributed ledger for internet of things. (May 2020) - Shahid, Furqan; Khan, Abid; Jeon, Gwanggil
Abstract: Distributed ledger (DL) technology can help us to overcome security and privacy issues in IoT systems, however, merging of these two technologies engenders certain challenges. Cryptocurrencies initiated DL technology to maintain a history of the financial transactions. The size of a DL in a cryptocurrency approaches to hundreds of GBs, whereas, IoT nodes are limited in storage. Similarly, cryptocurrencies incorporate computationally expensive consensus mechanisms, whereas, IoT nodes are limited in computation and energy. Furthermore, the classical DLs (like Bitcoin) are not quantum-resilient. This paper proposes a quantum-secure DL for IoT environments, namely DL-for-IoT . The core of our design is a novel one-time signature (OTS) scheme namely, DL-OTS, which is a compact and efficient scheme. DL-OTS offer 75% reduction in signature size and 76% reduction in signature creation time, as compared to the popular Winternitz-OTS + scheme. Furthermore, DL-OTS is an energy-efficient scheme, which saves 48.7% energy as compared to Winternitz-OTS scheme.